Effect of Premelting on Conductivity of DNA-Lipid Films. (1st April 2009) - Kasumov, A. Yu.; Nakamae, S.; Cazayous, M.; Kawasaki, T.; Okahata, Y.
Abstract : We have measured temperature-dependent (between 20 and 80 ∘ C) electrical conductivity and molecular structure (Raman spectroscopy) of DNA-lipid cast film. Our findings show that the conductivity is strongly influenced by premelting effects in the molecular structure starting near physiological temperatures (∼ 40 ∘ C), prior to the global DNA denaturation.